2006
DOI: 10.2754/avb200675040501
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals in Brown Bears from the Central European Carpathians

Abstract: The aim of the present study was to assess heavy metal load in the brown bear (Ursus arctos) living in the central European Carpathians. Between 2002 and 2004, fifteen bears were examined to evaluate the distribution of cadmium, lead, mercury and copper in the animals' muscles (diaphragm), spleen, liver and kidney. The highest content of cadmium, lead and mercury was found in the kidney (17.4 ± 5.2 mg·kg -1 , 1.16 ± 0.39 mg·kg -1 , 0.39 ± 0.25 mg·kg -1 ), whereas the lowest content of the metals was observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
2
5
1
Order By: Relevance
“…Also, all of the bears had much lower liver levels than the ones indicative of hepatic lesions in terrestrial mammals (>7 mg/g wet mass). [1] Cadmium Mean Cd concentrations in the muscles measured in this study were somewhat higher than the values found previously in two Croatian bears, [29] and brown bears from the Low Tatras, Slovakia, [20] but lower than those in bears from the Western Carpathian, Slovakia, [21] and Karelia, Russia. [18] Liver Cd concentration was comparable to the before mentioned reports, except for the much lower level reported for two brown bears from Croatia (0.347 mg/g wet mass) [29] probably due to the small sample size.…”
Section: Seleniumcontrasting
confidence: 68%
See 1 more Smart Citation
“…Also, all of the bears had much lower liver levels than the ones indicative of hepatic lesions in terrestrial mammals (>7 mg/g wet mass). [1] Cadmium Mean Cd concentrations in the muscles measured in this study were somewhat higher than the values found previously in two Croatian bears, [29] and brown bears from the Low Tatras, Slovakia, [20] but lower than those in bears from the Western Carpathian, Slovakia, [21] and Karelia, Russia. [18] Liver Cd concentration was comparable to the before mentioned reports, except for the much lower level reported for two brown bears from Croatia (0.347 mg/g wet mass) [29] probably due to the small sample size.…”
Section: Seleniumcontrasting
confidence: 68%
“…[16,17] Several published studies covered only the Carpathian and north-eastern Europe populations with a relatively small number of investigated bears (N D 15-20). [18][19][20] The exception was a study done by Zilin c ar et al [21] where 112 brown bears were sampled. The only report of Se in brown bears came from the measurements of three Asian animals, specifically from the Khabarovsk territory (east Russia).…”
Section: Introductionmentioning
confidence: 99%
“…However, because baseline concentrations were so low, concentrations in the top predator (lynx) were low. Similarly, top predator brown bears also had low concentrations in central Europe (0.01 μg/g, Celechovska et al, 2006).…”
Section: Biomagnification In Terrestrial Systemsmentioning
confidence: 99%
“…Soil, air and water analyses alone are inadequate for the assessment of the availability and potential toxicity of contaminants to humans and wildlife. [7,11] This is why the in vitro studies involving live animal tissues are of significance, and among them the quality parameters of spermatozoa assume considerable importance in this regard.…”
Section: Introductionmentioning
confidence: 99%